Nutritional evaluation of fermented palm kernel cake using red tilapia - Buchi, Iluyemi Florence; Musa, Mohamed Hanafi; Othman, Radziah; Kamarudin, Mohd Salleh (Academic Journals, 2010)
The use of palm kernel cake (PKC) and other plant residues in fish feeding especially under extensive aquaculture have been in practice for a long time. On the other hand, the use of microbial-based feedstuff is increasing. In this study, the performance of red tilapia raised on Trichoderma longibrachiatum fermented PKC (TL-PKC) was evaluated. Seven isonitrogenous and isocaloric diets were formulated. Reference diet, D1 had no PKC, while the other diets, D2 to D5 contained 10, 20, 30 and 40% fermented PKC (TL-PKC), respectively. All diets contained 1% chromic oxide as an inert marker. Red tilapias of average weight of 2.5 g were fed on these six diets for a period of 8 weeks. The fish were fed at 4% of their body weight, twice a day. There was no difference in mortality rate of fish on the various diets used. However, weight gain decreased with an increase of TL-PKC in diets. There were significant (P £ 0.05) differences in the apparent digestibility coefficient (ADC) of protein and dry matter between the reference diet and diet containing TL-PKC. The ADC of both protein and dry matter generally decrease when the percentage TL-PKC was increased in the test diets. There was also no significant difference in carcass protein content among fish on the various diets. However, there was a significant (P £ 0.05) increase in the levels of phosphorus, calcium and copper in the carcass of fish raised on TL-PKC, but the level of lipids was significantly reduced. Decreasing dry matter and protein digestibility with corresponding weight reduction may have resulted from increased crude fibre content of diets with TL-PKC.